Integrating Islamic Values into EFL Instruction: Applying the Spiral Andromeda Philosophy Across Curriculum Levels - Hasibuan, Kalayo; Fayza Nur Amalia; Helmalia Azahra; Muhammad Lowelfit; Yumna Arianti (Journal of Applied Linguistics, 2025)
This conceptual study explores the integration of Islamic values into English as a Foreign Language (EFL) instruction through the Spiral Andromeda Philosophy, a framework that emphasizes the interconnectedness of religious and secular knowledge. In Islamic educational institutions, language instruction is increasingly expected to contribute not only to linguistic competence but also to spiritual and ethical development. The Spiral Andromeda model supports this integration by aligning curriculum components—at the supra, macro, meso, and micro levels—with Islamic educational values. This study outlines practical strategies for curriculum design, instructional materials, teaching methods, and assessment practices that reflect both language goals and Islamic moral principles. Findings suggest that EFL instruction grounded in this framework encourages reflective learning, cultural relevance, and ethical communication, thereby promoting a more holistic form of education. However, challenges such as teacher preparedness, availability of contextual materials, and alignment with national language policies must be addressed. The discussion further connects this model to established educational theories such as Vygotsky’s Zone of Proximal Development and Freire’s critical pedagogy. The paper concludes by recommending institutional support, teacher training, and culturally relevant content development as critical components for successful implementation. The Spiral Andromeda Philosophy offers a transformative approach for faith-based institutions seeking to harmonize language learning with character formation, fostering learners who are both communicatively competent and morally grounded. Keywords : Islamic Education, EFL Instruction, Spiral Andromeda Philosophy, Value Integration, Holistic Learning.